2023
DOI: 10.32604/cmes.2023.023544
|View full text |Cite
|
Sign up to set email alerts
|

Brain Functional Networks with Dynamic Hypergraph Manifold Regularization for Classification of End-Stage Renal Disease Associated with Mild Cognitive Impairment

Abstract: The structure and function of brain networks have been altered in patients with end-stage renal disease (ESRD). Manifold regularization (MR) only considers the pairing relationship between two brain regions and cannot represent functional interactions or higher-order relationships between multiple brain regions. To solve this issue, we developed a method to construct a dynamic brain functional network (DBFN) based on dynamic hypergraph MR (DHMR) and applied it to the classification of ESRD associated with mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The results showed that the classification performance was best when L was set to 85 and s to 3, which is consistent with the research conclusion of Xi et al [ 23 ]. As L and s increase, the classification performance first improves and then deteriorates.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that the classification performance was best when L was set to 85 and s to 3, which is consistent with the research conclusion of Xi et al [ 23 ]. As L and s increase, the classification performance first improves and then deteriorates.…”
Section: Resultssupporting
confidence: 90%
“…Bian et al [ 22 ] extracted brain network multidimensional persistent features based on persistent homology with multi-threshold filtering (MTF) and identified brain connectivity patterns specific to Alzheimer’s disease. Xi et al [ 23 ] constructed dynamic hypergraphs and introduced hypergraph popular regularization and L1-norm regularization terms into the brain network construction model, extracting hypergraph features for the classification of patients with ESRDaMCI and health control (HC). Zhang et al [ 24 ] used graph theory to extract the AUC value of the topological properties within the sparse threshold range as a feature using the GRETNA toolbox to predict the degree of cognitive impairment in ESRD patients and HC individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline methods include Pearson correlation (PC), 14 sparse representation (SR), 15 graph regularization (MR), 18 sparse and hypergraph manifold regularization (SHMR), 19 and dynamic hypergraph manifold regularization (DHMR). 20 All methods adopted the same feature extraction and selection methods, used SVM for classification, and compared the final optimal results. The detailed classification performance is presented in Table 3, with the optimal results highlighted in bold.…”
Section: Contrast Experimentsmentioning
confidence: 99%
“…We evaluated the effectiveness of AMR by comparing it with five state‐of‐the‐art methods for constructing BFNs. The baseline methods include Pearson correlation (PC), 14 sparse representation (SR), 15 graph regularization (MR), 18 sparse and hypergraph manifold regularization (SHMR), 19 and dynamic hypergraph manifold regularization (DHMR) 20 . All methods adopted the same feature extraction and selection methods, used SVM for classification, and compared the final optimal results.…”
Section: Experiments and Analysismentioning
confidence: 99%
See 1 more Smart Citation